Giant concha bullosa: a curable cause of nasal obstruction - Ferreira, Ângela (2016)
Introduction: Nasal obstruction is a common problem in Portugal. It can have negative influences on quality of life and repercussions for family dynamics. It has several causes. Among them is concha bullosa. The objectives of this article are to describe a case of giant concha bullosa and to summarize the approach to the patient with nasal obstruction in primary care. Case description: A 50 year-old woman presented to a hospital emergency department because a blocked right ear. She had experienced chronic bilateral nasal obstruction, snoring and headaches. Right serous otitis media was diagnosed and the middle nasal turbinate was found to extend to the nasal vestibule. There were abundant secretions and adenoid hypertrophy was found on nasal endoscopy. She was treated with corticosteroids and decongestants and referred for otolaryngology consultation. Pharyngeal biopsy was not diagnostic. Computed tomography showed the existence of a right-sided giant concha bullosa. Surgery was performed with resolution of nasal obstruction, relief of headache, and improvement of snoring. Comment: Some patients may present complaints initially to the hospital emergency department. However it is important to stress the role of the family physician as health care provider and case manager. The initial history and physical examination are important in the investigation of complains of nasal obstruction. ‘Red flags’ must be investigated. If any of these are present or if there is an unsatisfactory response to medical therapy, the patient must be referred for specialist consultation. In this case, the evidence of unilateral serous otitis media required investigation for the exclusion of nasopharyngeal cancer. Anatomical variants are potentially curable causes of nasal obstruction and should be considered in the differential diagnosis of persistent nasal obstruction.